Graphics design work: service / Zamir Aizat Hamdan - Hamdan, Zamir Aizat (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Elevating the image of Bengoh Dam as one of the top tourist destinations in Sarawak is our key. To overcome its lack of a unique corporate identity, the proposed logo aims to capture the essence of its lush jungle setting. To enhance its visibility, Viva city serves as a strategic advertising point along with key routes to the main city. Through an integrated multimedia approach, blending captivating visuals and informative content, the initiative seeks to attract tourists by showcasing Bengoh Dam's scenic allure and natural wonders. Harnessing the power of advertising and multimedia, the goal is to attract visitors to the heart of Sarawak's natural beauty.